Disparities and Impact of Medicaid Expansion on Left Ventricular Assist Device Implantation and Outcomes. Issue 6 (June 2020) - Wang, Xiaowen; Luke, Alina A.; Vader, Justin M.; Maddox, Thomas M.; Joynt Maddox, Karen E.
Abstract : Background: Left ventricular assist device (LVAD) therapy is an increasingly viable alternative for patients who are not candidates for heart transplantation or who are waiting for a suitable donor. We aimed to determine whether there is an association between sex, race/ethnicity, insurance coverage, and neighborhood income and access to/outcomes of LVAD implantation. We further analyzed whether access to LVAD improved in states that did versus did not expand Medicaid. Methods and Results: Retrospective cohort study using State Inpatient Databases to identify patients 18 to 85 years of age admitted for heart failure, cardiogenic shock, or LVAD implantation from 2012 to 2015. Logistic regression analyses adjusting for age, all the sociodemographic factors above, medical comorbidities, and a hospital random effect were used to quantify odds of receipt of LVADs, as well as outcomes conditional on receiving an LVAD, for the sociodemographic groups of interest. A total of 925 770 patients were included; 3972 (0.43%) received LVADs. After adjusting for age, comorbidities, and hospital effects, women (adjusted odds ratio [aOR], 0.45 [0.41–0.49]), black patients (aOR, 0.83 [0.74–0.92]), and Hispanic patients (aOR, 0.74 [0.64–0.87]) were less likely to receive LVADs than whites. Medicare (aOR, 0.79 [0.72–0.86]), Medicaid (aOR, 0.52 [0.46–0.58]), and uninsured patients (aOR, 0.17 [0.11–0.25]) were less likely to receive LVADs than the privately insured, and patients in low-income ZIP codes were less likely than those in higher income areas (aOR, 0.71 [0.65–0.77]). Among those who received LVADs, women (aOR, 1.78 [1.38–2.30]), patients of unknown race or race other than white, black, or Hispanic (aOR, 1.97 [1.42–2.74]), and uninsured patients (aOR, 4.86 [1.92–12.28]) had higher rates of in-hospital mortality. Medicaid expansion was not associated with an increase in LVAD implantation. Conclusions: There are meaningful sociodemographic disparities in access and outcomes for LVAD implantation. Medicaid expansion was not associated with an increase in LVAD rates.